2021
DOI: 10.5603/fm.a2020.0106
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts on the morphology of popliteus tendon and its clinical implications

Abstract: In this review we described the anatomy and biomechanics of popliteus muscle and its tendon. Furthermore, we combined the anatomy with clinics and discussed a wide spectrum of disorders regarding the popliteus and its musculotendinous complex.There are three main anatomical regions of the popliteus musculotendinous complex: the proximal origin, the mid-portion, the distal part on the tibia. The unique localization and various origins of the tendon, connected with structures such as fibular head, Wrisberg, Hump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Lower concentrations of collagen in the tendon suggests reduced development or maturation, which could lead to reduced function and tendinopathy. Due to the role of tendons in the transfer of muscle force to the appropriate skeletal structure, a reduction of tendon maturation represents a significant threat to the musculoskeletal system (Snedeker and Foolen, 2017;Zabrzyński et al, 2018Zabrzyński et al, , 2020. Although caution should be taken in the evaluation of the tendon data in the current study due to modest group n's, the reported effect sizes are suggestive of an influence of ELS on this variable.…”
Section: Discussionmentioning
confidence: 77%
“…Lower concentrations of collagen in the tendon suggests reduced development or maturation, which could lead to reduced function and tendinopathy. Due to the role of tendons in the transfer of muscle force to the appropriate skeletal structure, a reduction of tendon maturation represents a significant threat to the musculoskeletal system (Snedeker and Foolen, 2017;Zabrzyński et al, 2018Zabrzyński et al, , 2020. Although caution should be taken in the evaluation of the tendon data in the current study due to modest group n's, the reported effect sizes are suggestive of an influence of ELS on this variable.…”
Section: Discussionmentioning
confidence: 77%
“…The sports like tennis, basketball and downhill running may put additional stress on the tendon of popliteus. 6 The present study provided the data about the neurovascular structures in relation to the popliteus and it is believed that these details are clinically important for the effective treatment of the popliteus muscle spasticity. 15 Popliteus muscle tendon complex is a landmark to the operating surgeon during the sling reconstruction of popliteus tendon.…”
Section: Discussionmentioning
confidence: 82%
“…But its involvement is ignored in the complex injury of the knee joint. 6 The isolated involvement of popliteus is seen in sports injuries and it may be misinterpreted as a tear of lateral meniscus. The sports like tennis, basketball and downhill running may put additional stress on the tendon of popliteus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is rare, CPN can be also injured during large surgical procedures, like posterolateral corner reconstruction or high tibial osteotomy [ 31 32 ].…”
Section: Peroneal Neuropathymentioning
confidence: 99%